Ratio Analysis of Regional Dependence and Independence in Measuring the Regional Financial Capability of the Jambi Provincial Government - Iskandar Nasution; Bambang Niko Pasla; Fahmi Rasid; Fathiyah Fathiyah; Muhammad Arif (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2022)
Introduction/Main Objectives: This study aims to analyze the ratio of regional dependence and independence in measuring the financial capacity of the Jambi Provincial Government for the 2016 - 2020 Fiscal Year. Background Problems: How big is the ratio of the contribution of Regional Original Revenue (PAD) to transfer funds from the center in the Jambi Provincial Government APBD in funding development financing for 2016-2020?. Research Methods: The research is quantitative using secondary data in the form of Regional Original Income and transfers funds from the Jambi Province Government Budget Realization Report for the 2016 - 2020 Fiscal Year. Finding/Results: Based on the results of the ratio analysis, the degree of financial dependence of the Jambi Provincial Government in the 2016 - 2020 fiscal year is classified as moderate, with an average overall ratio of 63.60%, meaning that the Jambi Provincial Government in carrying out development financing is still dependent on transfer funds from the center. Meanwhile, the degree of regional financial independence is also classified as moderate/participatory, with an average overall ratio of 57.13%. Conclusion: The contribution of regional Original Revenue in funding development financing cannot be entirely relied upon and still relies on transfer funds from the center.